Premium rates and selection in specialty crop insurance markets: Evidence from the catastrophic coverage participation. (May 2021) - Yu, Jisang; Sumner, Daniel A.; Lee, Hyunok
Highlights: We examine the crop insurance choices of specialty crop growers. Lower expected returns from Buy-up products lead to more CAT participation. Due to the self-selection, CAT tends to have greater underwriting gains. Abstract: Catastrophic coverage, fully-subsidized insurance that provides indemnities when yields fall below 50% of historical averages, has been the most widely used crop insurance product among specialty crop growers in the United States. Patterns in catastrophic coverage across a variety of fruit, vegetable, tree nut and horticultural crops and indicate that expected returns to "investing" in subsidized crop insurance affect the use of insurance. Our simple model shows that smaller net returns from higher coverages, imply more catastrophic and free coverage participations. Our econometric estimation uses observations of insured acreage, liabilities, indemnities, and premiums across 20 major crops and more than one thousand counties, over all the 23 years since catastrophic coverage became available. We find that a 10% reduction in the ratio of the indemnities to the premiums of non-catastrophic coverages, which implies a 4% reduction in expected returns to growers, leads to larger catastrophic coverage shares by almost one percent. Panel quantile regressions show that the result is robust to distributional assumptions. Estimation using subsamples and alternative specifications further confirm the robustness of our results. The conceptual and empirical results demonstrate the degree to which farms self-select into crop insurance products that provide greater expected payouts. Our empirical results also indicate that catastrophic coverage generates greater underwriting gains, which affects the reinsurance fund allocation of private insurers.